2011
DOI: 10.1093/carcin/bgr079
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of p38γ and p38δ involvement in cell transformation processes

Abstract: The p38 mitogen-activated protein kinase (p38MAPK) signal transduction pathway is an important regulator of cell processes, whose deregulation leads to the development and progression of cancer. Defining the role of each p38MAPK family member in these processes has been difficult. To date, most studies of the p38MAPK pathways focused on function of the p38α isoform, which is widely considered to negatively regulate malignant transformation; nonetheless, few reports address the p38γ and p38δ isoforms. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…Protein transfection in MEF and retroviral expression of macrophages were carried out as described (15,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein transfection in MEF and retroviral expression of macrophages were carried out as described (15,24).…”
Section: Methodsmentioning
confidence: 99%
“…p38δ-null mice show reduced susceptibility to skin carcinogenesis (14). However, studies in immortalized mouse embryonic fibroblasts and in K-Ras-transformed cells lacking p38γ or p38δ have indicated that these kinases can also inhibit tumor development (15). p38γ and p38δ are also expressed in immune cell lines and primary immune cells, and both are activated in myeloid cell lines in response to LPS (16,17).…”
mentioning
confidence: 99%
“…p38g regulates oncogenic proteins involved in colorectal cancer development, such as K-Ras, which is mutated in 50% of colon cancers (24). Nonetheless, studies in immortalized mouse embryonic fibroblasts and in K-Ras-transformed cells lacking p38g or p38d indicated that these kinases can also inhibit tumor development by regulating processes associated with malignant cell transformation such as proliferation, contact inhibition and/or migration (25). These findings suggest that p38g and p38d are implicated in linking tumor promotion and/or progression and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that they can play a tumor suppressor role inhibiting cell migration, MMP2 secretion and tumor growth in MEFs (24). In contrast, p38␦-null mice are more resistant to skin tumor development (25) and colon cancer development is impaired in p38␥/␦-deficient mice (26).…”
mentioning
confidence: 99%